Citizenship and constitutional law - Shaw, Jo, 1961- (Constitutional law (Cheltenham, England) ;, 2018)
This research review highlights the complex, dynamic relationship between citizenship - as membership status - and the constitutional law that provides the cornerstone of all polities. It shows the many different ways in which we must use constitutional law in order to fully understand how one becomes a citizen, and what the meaning of citizenship is. It also analyses the key works which cover national, transnational and international aspects of the topic, providing a particular focus on how constitutional law constructs and upholds the range of citizenship rights. This research review will be a valuable source of reference for students, academics and practitioners interested in citizenship and constitutional law.